O processamento do tempo verbal nos afásicos não fluentes - Pessoa, Luciane Spinelli de Figueiredo (2012)
This work lies within the Experimental Psycholinguistics theory, specifically in the investigation of mental processes related to the language comprehension in adults with language deficits. This study focuses on the investigation into the sentence processing of syntactic and semantic aspects by subjects with non-fluent aphasia. Specifically, we intended to understand how these aphasic subjects' language works, when they read congruent and incongruent sentences, with respect to the semantic relation between tense and adverb of time and if the the adverb in the sentence somehow interferes on the aphasic subjects processing For such purpose, we carried out four experiments using self-paced reading and acceptability judgment and we used as independent variables: (a) Group (Control Group/ Aphasic Group), Congruent Sentence/ Incongruent Sentence), (c) Tense (Past Tense/ Future Tense). In two experiments, the aphasic subjects were exposed to sentences in which the adverb. terday Julia bought a car at Fiat/Yesterday Paul was going to buy apples at Hiper.), among these sentences there were 8 congruent ones and 8 incongruent ones concerning the adverb and the tense, and 32 fillers. In the other two experiments, we used congruent and incongruent sentences concerning the semantic relationship between verb and adverb, in which the verb precedes the adverb (Paul did the homework yesterday afternoon. / Joey was going to buy a motorcycle at Honda yesterday.). Our results, supported by on-line and off-line measures, indicate that non-fluent aphasic subjects from this study have, in general, difficult to perceive incongruence with regard to the semantic relationship between tense and adverb of time, regardless of the position of the adverb and tense. In the self-paced reading, that is, the on-line measure, the aphasic subjects showed some sensitivity to the tense incongruence when the verb was presented in a single way. On the other hand, when they read sentences in which the tense was presented by periphrasis, they showed no sign of sensitivity - unlike the control group who showed sensitivity to the tense incongruence in all experiments. The off-line measures, obtained through the acceptability judgment, reveal that the aphasic subjects from this study judge incongruent sentences as congruent ones, ie, the results show that there is, on the part of the aphasic subjects, difficulty in processing the semantic information integration between adverb and tense and hence insensitivity to perceive tense incongruence regardless of the used verb form and the sentence presentation order - adverb preceding verb or vice versa The results of this study contribute to the theoretical discussion on the tense processing by the aphasic agrammatic speakers, since they provide data about the real-time processing and show that the tense understanding in sentences is compromised regardless of these theory and refuting Faroqi-Shah and Dickey's (2009) premise. In addition, this study points out that, in order to obtain a better understanding by the aphasic in question, we should opt for the use of sentences with verbs in simple form, both in clinical speech therapy and in general situations of communication with the subject in question. We consider that other studies should be carried out focusing the reference of tense in verbs and periphrastic forms equivalent to each other in relation to semantic notions of tense, that is, with equivalent notions of tense and aspect.